Analysis Of Thresholds In Rule-Based Antilock Braking Control Algorithms. (2020) - Challa, Akhil; Ramakrushnan, Karthik; Subramanian, Shankar C.; Vivekanandan, Gunasekaran; Sivaram, Sriram
Abstract: An Antilock Braking System (ABS) is an Active Vehicle Safety System (AVSS) employed to prevent wheel lock in road vehicles. Wheel lock is undesirable as it may lead to loss of vehicle steerability and directional stability. These become critical in Heavy Commercial Road Vehicles (HCRVs) as unintentional yaw motion resulting from directional instability may also lead to vehicle roll-over. ABS algorithms are broadly classified as Model-Based Algorithms (MBAs) and Rule-Based Algorithms (RBAs). MBAs are typically physics based and employ vehicle dynamic models. RBAs, which are currently predominantly used in vehicles, are threshold based. RBAs require measurement of wheel speed that is readily available, while MBAs require real time information on vehicle parameters and tire models. Most commercially available RBAs are proprietary and the details are not revealed. This has motivated the present study, and the physical significance of the wheel slip and wheel acceleration thresholds used in RBAs are clearly identified, backed by experiments from a Hardware-in-Loop (HiL) pneumatic brake setup along with IPG TruckMaker®, a software for vehicle dynamic simulation. This study is an important first step in developing an advanced RBA for HCRVs.